Hydrothermal Liquefaction of Scrap Tires: Optimization of Reaction Conditions and Recovery of High Value-Added Products - Chen, Rongjie; Li, Hang; Li, Kaile; Zhang, Shiyu; Li, Qinghai; Zhou, Hui; Zhang, Yanguo (Frontiers in Energy Research, 2022)
Response surface method (RSM) was proposed to investigate the conversion of scrap tire via hydrothermal treatment. Temperature was the dominant factor in the process. The liquefaction rate increased sharply with temperature and exceeds 40 wt.% in the supercritical region ( >374.3°C). A maximum of more than 40 wt.% liquefaction rate was obtained when the tire was kept at 399°C for 60 min with the water/tire mass ratio of 10.8/1. Subsequently, the analysis of solid phase and liquid products at 360 and 400°C was carried out. The thermal stability of natural rubber in tire is significantly deteriorated after hydrothermal treatment. The hydrothermal process of rubber includes chain cleavage, particle hydrolysis, and carbon nanospheres formation, growth and agglomeration. The liquid products including carotenoids, ketones, and aromatic compounds, the ratio of which can be adjusted according to the temperature.